Impact of automated valuation model on valuation for residential property - Lim, Zheng Jie (2023)
This research was carried out to study the impact of the automated valuation model towards the valuation practice in Malaysia. Four factors had been tested which are cost, time, accuracy and knowledge. This study had applied both qualitative and quantitative research method. The target population of this research is Malaysian valuers who are aware of the AVM. Primary data of this research was obtained through the distribution of 45 copies of questionnaires and was analyzed using the SPSS software. The constructs of the questionnaire were reliable as the Cronbach’s Alpha value of all the factors were above 0.6. The data analysis applied for this research are the relative importance index and content analysis. Through the relative importance index, the four factors were ranked from most important to least important and the ranking is as follow: accuracy, time, knowledge, cost. As for the content analysis, it analyzed the opinions of valuers towards the threat on job opportunities. In short, the AVM poses low threat for the time being but it might develop and emerge as a bigger threat in the future. This study serves as an update to earlier research on the automated valuation model and offers data for upcoming academics who want to study the model in the future. There are extremely few publications and articles about valuation, particularly for the automated valuation model, due to the nature of the sector. As a result, this study contributes to the expansion of knowledge about the automated valuation model. Additionally, valuation firms who are thinking about using the automated valuation model can put this research to use. The findings of this study outline the benefits and drawbacks of the automated valuation model, allowing valuation business owners to weigh the pros and downsides before deciding whether to use the model or not.